Interview with Lucky Lartey : discussing Ewe & Ga rhythms, Sankofa architecture - (:unkn) unknown (My University, 2021)
(AUDIO) Dancer Lucky Lartey interviewed by the author, Deirdre Molloy. Recorded remotely using Zoom software – Lartey in Sydney Australia, Molloy in Toulouse, France. Audio EQ and production by Deirdre Molloy. Discussion includes dance video commentary.
Keywords: African Research